2018
DOI: 10.1111/asj.13147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antidesma thwaitesianum Muell. Arg. pomace as a source of plant secondary compounds on digestibility, rumen environment, hematology, and milk production in dairy cows

Abstract: Mao pomace meal (MPM) contains condensed tannins and saponins at 92 and 98 g/kg, respectively, and these substances can be used to manipulate ruminal fermentation in ruminant. Four multiparous lactating Holstein cows with 45 ± 5 days in milk were randomly assigned according to a 4 × 4 Latin square design to receive four different levels of MPM supplementation at 0, 100, 200, and 300 g/head/day, respectively. Cows were fed with concentrate diets at 1:1.5 of concentrate to milk yield ratio and urea‐treated (3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…Similarly, Piamphon et al [ 38 ] noted that hemoglobin and hematocrit were unaffected when feeding yeast-fermented Napier grass mixed with cassava root to beef cattle. In comparison to the previous findings, all of the hematological indices for ruminants remained within their respective ranges [ 17 , 39 , 40 ]. Based on these findings, it can be assumed the addition of YERSEK at any level to the diet of dairy cows is non-toxic.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Similarly, Piamphon et al [ 38 ] noted that hemoglobin and hematocrit were unaffected when feeding yeast-fermented Napier grass mixed with cassava root to beef cattle. In comparison to the previous findings, all of the hematological indices for ruminants remained within their respective ranges [ 17 , 39 , 40 ]. Based on these findings, it can be assumed the addition of YERSEK at any level to the diet of dairy cows is non-toxic.…”
Section: Discussioncontrasting
confidence: 72%
“…Dietary regimens were based on YERSEK levels of 0%, 10%, and 20% in concentrate diets ( Table 1 ). Mid-lactation crossbred dairy cows were fed concentrate diets with a milk production ratio of 1:1.5 [ 16 , 17 , 18 ] and ad libitum rice straw as roughage. At 7:00 a.m. and 4:00 p.m. each day, diets were provided.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, TCM was an alternative animal feed that did not receive a negative response regarding its palatability, as there were no negative effects on feed intake and nutrient intake. Similarly, Gunun et al [ 28 ] found that CT-containing seed meal from Antidesma thwaitesianum Muell. Arg.…”
Section: Discussionmentioning
confidence: 93%
“…Ruminal protozoal population at 2 h and 4 h after incubation with various doses of hog plum supplementation are shown in Table 3. Numerous tropical plants consisting great contents of saponins have become interesting choices for interrupting protozoa in the rumen (Gunun et al, 2019). At 2 h after incubation, there were no changed on protozoal counts (P>0.05), whereas the reduction of protozoal counts were found when added hog plum at 4 h after incubation (P<0.05).…”
Section: Rumen Parametersmentioning
confidence: 98%
“…Tropical plants consist of high contents of saponins which have become noticeable choices for prohibiting protozoa in the rumen (Gunun et al, 2019). These possibly be that these compounds may disturb the activity of ruminal protozoa, likely by attaching the proteins and enzymes of the protozoal membranes (Hristov et al, 2013).…”
Section: Advances In Animal and Veterinary Sciences December 2019 | Vmentioning
confidence: 99%